Effect of synthesis on the antimicrobial response of β-TCP/Mg with potential applications in the regeneration of dental tissue: 3D printing of ceramic paste in a β-TCP/Mg/bioglass system (2023)
This work aims to determine the most suitable synthesis route using calcium phosphate ceramic pastes with Mg to generate scaffolds with antimicrobial activity against Candida albicans and Streptococcus mutans from ceramic powders obtained by sol–gel (SGM) and self-combustion (SCM) routes. Calcium phosphates in SGM processes present a mixture of several types of crystalline phases, whereas SCM leads to a single β-TCP phase. The in vitro antimicrobial activity study showed that CP-C/Mg by SCM had a better effect than CP-S by SGM against C. albicans. For S. mutans, no inhibitory effect was found. In addition, the co-culture of these two species showed an inhibitory effect on the evaluated materials. These results formulated a ceramic paste based on the β-TCP/Mg/ bioglass system by the design of experiments to obtain 3D-printed scaffolds. These ceramic materials show promise as devices for the regeneration of dental tissues.